2010
DOI: 10.1248/bpb.33.1835
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3,4,6-Penta-O-galloly-beta-D-glucose Suppresses Hypoxia-Induced Accumulation of Hypoxia-Inducible Factor-1.ALPHA. and Signaling in LNCaP Prostate Cancer Cells

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a heterodimeric transcription factor that plays a role in cell survival in response to hypoxia and is overexpressed in many human solid cancers. HIF-1 consists of two subunits, HIF-1a and HIF1b.1) HIF-1a is steadily degraded by the ubiquitin-proteasome pathway under normoxic condition and stabilized under hypoxic condition, in contrast to HIF-1b, which is constitutively expressed. In the presence of iron and oxygen, HIF-1a is hydroxylated by prolyl hydroxylase domain (PHD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The VEGF production level measurement methods was previously described in our other study [39]. The culture supernatants was added in a 96-well plate, and reacted with dilution buffer and incubation buffer at room temperature for 2 h. The wells were then washed four times with washing buffer, and then biotin conjugate was added to each well at room temperature for 1 h. After washing, the stabilized chromogen was added into each well and reacted for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The VEGF production level measurement methods was previously described in our other study [39]. The culture supernatants was added in a 96-well plate, and reacted with dilution buffer and incubation buffer at room temperature for 2 h. The wells were then washed four times with washing buffer, and then biotin conjugate was added to each well at room temperature for 1 h. After washing, the stabilized chromogen was added into each well and reacted for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that PGG reduces the expression of PI3K as well as phosphorylation of AKT and mammalian target of rapamycin (mTOR) [39]. It is likely that PGG suppress IAV-induced cofilin-1 phosphorylation via inhibition of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour hypoxia is caused by an imbalance between cellular O 2 use and supply rates in the cells via activation of the transcription factor HIF-1␣. HIF-1␣ is over expressed in many types of cancers and plays an important role in angiogenesis by regulating VEGF expression [5]. HIF-1␣ activates transcription of the promoter of vascular endothelial growth factor (VEGF), a key factor in tumour angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It deactivates transcription of the promoter of VEGF. Hypoxia-inducible factor-1 is a heterodimeric transcription factor that plays a role in cell survival in response to hypoxia and is over expressed in many human solid cancers [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation